Effect of symbiont-targeted control of Halyomorpha halys on the co-occurring pentatomid community - Prieto, Sofia V.; Orrù, Bianca; Gonella, Elena; Alma, Alberto (Frontiers in Insect Science, 2025)
Several native species in the family Pentatomidae are recorded in north-western Italy, associated with different crops. The arrival of Halyomorpha halys led to a reorganization of the role of other pentatomids, some of them becoming secondary pests. Symbiont-targeted control strategies, which disrupt beneficial interactions in stink bugs, have so far been applied to H. halys. However, this approach could also be useful for controlling other pentatomid pests. Additionally, the effects of this strategy on non-target stink bug species need further investigation to assess its potential impact on agroecosystems. Here the effect of symbiont disruption was assessed for stink bugs that share host crops (e.g., hazelnut, wheat, soybean) or the environment (especially wild areas adjacent to crops) with H. halys in north-western Italy (Carpocoris purpureipennis, Dolycoris baccarum, Graphosoma italicum, Palomena prasina and Rhaphigaster nebulosa). Their symbionts were identified as allied to the genus Pantoea through 16S rRNA gene sequencing and also other bacteria were detected in the V4 ventricle of the midgut. Strikingly, variable symbiont infection was found across species. Laboratory tests were conducted assessing the consequences of symbiont deprivation during the first nymphal instar. Egg masses treatment with an anti-symbiont formulation affected hatching rates in D. baccarum and G. italicum, while the mortality rates during the first instar increased in C. purpureipennis and G. italicum. A correspondence between mortality induction and the alteration of symbiont infection rates was observed, with species showing the highest infection drop being the most affected by treatments. These results provide new insights into pentatomid symbionts and reveal significant variability in the response to symbiosis disruption, likely due to species-specific intensity of symbiotic interactions. The consequences of this variability are discussed.